Antecedent Factors of Intention to Use Digital Wallets and the Moderating Role of Consumer Trust - Fitriani, Diah; Astuti, Puji (Formosa Journal of Sustainable Research, 2024)
The Covid 19 (Coronavirus Disease That Was Discovered In 2019) pandemic has encouraged people to have high digital literacy. Since entering the New Normal Era, people as buyers must also avoid and make transactions using cash and make more use of digital payments, one of which is through digital wallet platforms. The aim of this research is to explore the antecedent factors that influence the intensity of digital wallet use and also to look at the moderating role of customer trust. This research was conducted on 194 respondents who are digital wallet users. This research uses quantitative methods using covariance based structural equation modeling (SEM) analysis tools. The research sample was Gopay/OVO/Dana digital wallet users aged 17 to 45 years and had used digital wallets for at least 6 months. Several variables in this research were confirmed to be antecedent factors for the intensity of digital wallet use, where attitude was proven to have a positive influence on intention to use and of all the factors that influence attitude, perceived usefulness is the most dominant. Some of the recommendations from this study are to continue to increase the benefits that digital wallet users can experience so that they will improve attitudes to increase the intensity of payments using digital wallets